The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.3389/fmicb.2017.00806
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Polymorphism in Wine Yeasts: Mechanisms and Methods for Its Detection

Abstract: The processes of yeast selection for using as wine fermentation starters have revealed a great phenotypic diversity both at interspecific and intraspecific level, which is explained by a corresponding genetic variation among different yeast isolates. Thus, the mechanisms involved in promoting these genetic changes are the main engine generating yeast biodiversity. Currently, an important task to understand biodiversity, population structure and evolutionary history of wine yeasts is the study of the molecular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 259 publications
(322 reference statements)
2
33
0
Order By: Relevance
“…3.1. Differentiation of non-Saccharomyces strains by random amplified polymorphic DNA polymerase chain reaction (RAPD-PCR) Molecular techniques have been successfully applied by several authors to identify the yeast biodiversity in diverse environments, not only for species identification, but also for strains identification (Andrighetto, Psomas, Tzanetakis, Suzzi, & Lombardi, 2000;Grando, Ubeda, & Briones, 1994;Guillamón & Barrio, 2017;Suzzi et al, 2000;Úbeda, Maldonado Gil, Chiva, Guillamón, & Briones, 2014), due to the fact that probiotic activity it is associated to strain-level.…”
Section: Resultsmentioning
confidence: 99%
“…3.1. Differentiation of non-Saccharomyces strains by random amplified polymorphic DNA polymerase chain reaction (RAPD-PCR) Molecular techniques have been successfully applied by several authors to identify the yeast biodiversity in diverse environments, not only for species identification, but also for strains identification (Andrighetto, Psomas, Tzanetakis, Suzzi, & Lombardi, 2000;Grando, Ubeda, & Briones, 1994;Guillamón & Barrio, 2017;Suzzi et al, 2000;Úbeda, Maldonado Gil, Chiva, Guillamón, & Briones, 2014), due to the fact that probiotic activity it is associated to strain-level.…”
Section: Resultsmentioning
confidence: 99%
“…The stresses that yeast cells encounter during wine fermentations include the elevated content of sugar in grape musts, the high ethanol concentrations achieved, the temperature of the different fermentation types, and the sulfite added as an antimicrobial and antioxidant agent (Bauer and Pretorius, 2000;Divol et al, 2012). These environmental stresses exerted for hundreds of years and thousands of generations have caused wine yeasts to evolve rapidly, shaping their genome through different genetic mechanisms (Marsit and Dequin, 2015;Guillamón and Barrio, 2017;Legras et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…While industrial Saccharomyces hybrids inherit good fermentation performance such as growth ability at lower temperatures [69][70][71][72][73], hybridization gives rise to instability of the chromosomes, which in turn results in spore unviability [74,75]. It has been also reported that sporulation efficiency is significantly anticorrelated with the fraction of the genome associated with large (>20 kb) amplifications and deletions [76]. Aneuploidies and massive copy number variations are also seen in inter-strain hybrids of S. cerevisiae.…”
Section: Difficulty and Contradiction In Conventional Crossbreedingmentioning
confidence: 99%